IMPLICATIONS OF MANTLE PLUME STRUCTURE FOR THE EVOLUTION OF FLOOD BASALTS - Campbell I.H.; Griffiths R.W. (My University, 1990)
We discuss the geological, geophysical, and petrological observations that constrain the nature of mantle convection in plumes, and show how theoretical models of mantle plumes have developed over the past three decades. The large volumes of lava emplaced in geologically short periods as flood basalts are generated mainly by decompression melting of abnormally hot mantle brought to the base of the lithosphere by plumes. We present new results from the application of McKenzie and O'Nions' (1991) rare earth element inversion scheme to the geochemistry of flood basalts to infer the amount of mantle melting and the depth interval over which it occurred. Our survey covers flood basalts from the Archaean to the Tertiary. The abundance of geochemical data from the Siberian Traps (250 Ma) and from the Keweenawan (1095 Ma) enables us to infer the temporal evolution of mantle melting in these two flood basalt provinces. We find that three quarters of the samples from flood basalts can be modeled by single-stage melting of asthenospheric mantle. The remainder require enrichment by small amounts of metasomatic melts emplaced in the lithospheric mantle by an earlier phase of minor (0.3%) melting at depths where garnet is stable. The mantle melting responsible for flood basalts starts at depths of 110 km or more beneath the surface, and is consistent with enhanced mantle potential temperatures of 1450-1550°C. Melting continues to depths of 70-30 km. At least some lithospheric thinning is required to explain both the geochemistry of the melts and the high rate of generation of flood basalts.
Keywords: Archaean; Precambrian::Archean; Докембрий::Архей